Analisis Quality Control Pada Proses Sewing Dengan Statistical Process Control (SPC) dan 5-Why’s Analysis: (Studi Kasus: PT. YZ Tbk.) - Ayu Anggraeni Sibarani; Vendy Mohammad Abdul Fatah; Dewi Tria Setyaningrum (Journal of Research in Industrial Engineering and Management, 2023)
PT. YZ Tbk. is a textile company headquartered in Sukoharjo, Central Java. The problem that exists in the company is the presence of defective products that cannot be avoided. Based on observations made on the sewing process in the garment section 2, there are problems related to quality control. There is product damage caused by various factors such as human factors, machines, raw materials and methods. If a defective product is found, the product will be repaired immediately until it is felt that the product meets the quality standards set by the company and the quality standards requested by consumers. This study aims to provide suggestions and recommendations for improvement efforts made to companies and formulate repair solutions using a statistical process control approach to reduce the number of defects that occur and meet company targets. The results of this study are that there are two types of defects that have the most defects and suggestions for improvement are given to reduce defects in the form of evaluation and repair, checking before production, and tightening inspections on the production line.